Disposição no solo e potencial fertilizante de um resíduo da indústria de biodiesel - Santos, Marcos Leandro dos (2014)
The biodiesel production generates large volumes of residues, which when improperly disposed have potential for environmental contamination. The objectives of this study were to evaluate the adding sawdust filtration untreated with a Oxisol and with an Paleudalf, producing an organic compound from the mixture of sawdust filtration with manure aiming to know the immediate potential and residual fertilizer of this organic compound in canola cultivated in these two soil types. Soil samples were placed in respirometric flasks and added 2; 4 and 8 t ha-1 sawdust filtration with and without addition of N, P and K recommended for the culture of canola. During 120 days we quantified C-CO2 production, the dynamics of these nutrients and the concentration of heavy metals. In pots in a greenhouse, the organic compound produced was mixed with these soils at planting or six months before. The doses were 0, 0.6, 1.2, 2.4 and 4.8 t ha-1, with or without supplemental N, and we quantified the availability of nutrients in the soil, the accumulation of dry mass and nutrients in tissues of canola. The biodegradation of sawdust filtration in the soil was high but limited by K in Oxisol and by P in Paleudalf. The addition of this residue in both soils cause reduced availability of N, K in the Oxisol, but did not increase the levels of heavy metals. The organic compound produced presents characteristics that allow its use in agriculture and its addition to soils at the time of sowing or six months before increases the availability of N, P and K, and replaces total or partially the mineral fertilization of canola.